Analysis of The Need for Accelerated Learning Model Based on Double Intelligence in Learning Arts of Middle Music - Venny Ribka Wisudarni; Harun Sitompul; Julaga Situmorang (Britain International for Academic Research (BIAR) Publisher, 2020)
This study aims to analyze the needs of the development of accelerated learning models based on multiple intelligences. The study was conducted by survey method in 9 (nine) Junior High Schools in Serdang Bedagai Regency. The research subjects were 18 class teachers who taught Art learning. The object studied is the response of the principal and teachers to the development of accelerated learning models based on multiple intelligences, the tendency of teachers to apply thematic models in learning in schools, student reasoning, and student character. Data collected by interview, questionnaire, observation, and test. Data were analyzed descriptively. The analysis shows that (1) school principals have not yet fostered the development of accelerated learning learning models, so they support development efforts, (2) teachers have not yet developed and used thematic models, so they support and express readiness to be involved in development, (3) learning models used by teachers so far there have been no indications leading to accelerated learning models based on multiple intelligences.